Дослідження геоелектричними методами інженерно- геологічного стану південно-західного Кривбасу. Частина 4.Використання потенціальних полів при вивченні сучасної тектоніки - Пігулевський, П.Г.; Свистун, В.К.; Кирилюк, О.С. (Геоінформатика, 2017)
Проаналізовано можливості ефективного використання геоелектричних методів та обробки цифрових моделей потенціальних фізичних полів. Трансформації гравітаційного поля у вигляді локальної складової дають змогу вивчати особливості геологічної будови кристалічного фундаменту й осадового чохла території південно-західної частини Кривбасу, виділяти розривну тектоніку, підняття і опущені блоки фундаменту. За результатами якісної й кількісної інтерпретації електророзвідки ВЕЗ разом з локальною складовою гравітаційного поля отримують додаткову інформацію про структуру водоносного комплексу та його взаємозв’язок з фільтраційними водами з відвалів, хвостосховищ і ставків-накопичувачів. За запропонованою технологією досліджень геоелектричними методами можна оперативно виявляти й картувати зони підтоплення під час комплексного вивчення впливу техносфери на геологічне середовище Кривбасу, оцінювати ступінь взаємозв’язку поверхневих і підземних вод з фільтраційними потоками з відвалів, хвостосховищ і ставків- накопичувачів для вирішення питань екологічної безпеки й сільськогосподарських виробництв. Анализируются возможности эффективного использования геоэлектрических методов и обработки цифровых моделей потенциальных физических полей. Трансформации гравитационного поля в виде локальной составляющей позволяют изучать особенности геологического строения кристаллического фундамента и осадочного чехла территории юго-западной части Кривбасса, выделять разрывную тектонику, поднятия и опущенные блоки фундамента. По результатам качественной и количественной интерпретации электроразведки ВЭЗ вместе с локальной составляющей гравитационного поля получают дополнительную информацию о структуре водоносного комплекса и его взаимосвязи с фильтрационными водами из отвалов, хвостохранилищ и прудов-накопителей. Предложенная технология исследований дает возможность оперативно выявлять и картировать зоны подтопления геоэлектрическими методами при комплексном изучении влияния техносферы на геологическую среду Кривбасса, оценивать степень взаимосвязи поверхностных и подземных вод с фильтрационными потоками из отвалов, хвостохранилищ и прудов-накопителей при решении вопросов экологической безопасности и сельскохозяйственных производств. Goal and tasks. A joint analysis of the results of different geo-electric studies and potential physical fields for the study of modern tectonic and geodynamic processes in the southwestern part of Krivbass in solving environmental safety and agricultural purposes. Method. Calculation and creating of maps of the gravitational field and its local component for the analysis of the features of the geological structure of the crystalline basement and sedimentary cover of the territory of the southwestern part of Krivbass. Isolation of rupture tectonics, raised and lowered foundation blocks. Performing a joint interpretation of geoelectric and gravimetric materials to determine the relationship between changes in the geoelectric parameters of the geological environment and the time-space changes in the hydrogeological situation, caused by active tectonic disturbances and geodynamic processes occurring in the upper part of the earth’s crust. Results. Interpretation of the local component of the gravitational field made it possible to establish in the study area the distribution of fault directions corresponding to the fault system by K.F. Tyapkin. Constructed maps based on the results of qualitative and quantitative interpretation of electrical exploration of the VES and the local component of the gravitational field made it possible to obtain additional information on the structure of the water-bearing complex and their relationship with filtration waters from dumps, tailing ponds and storage ponds. On these maps, together with the results of previous studies, it was possible to clarify and specify the hydrogeological features of the investigated area both in space and over a four-year period (from 2008 till 2012). Practical significance and conclusions. The proposed research technology allows us to quickly detect and map the zones of underflooding by geoelectrical methods in a comprehensive study of the influence of the technosphere on the geological environment of Kryvbas, to map the degree of interconnection between surface and groundwater with filter flows from dumps, tailing ponds and storage ponds in solving environmental safety and agricultural planning problems.